The extent FTSE100 companies are using countertrade strategically as method of internationalisation - Young, Derren (2006)
The aim of this research project is to investigate how the UKÃÂÃÂÃÂÃÂ¢ÃÂÃ¢ÂÂÃÂÃ¢ÂÂ¬ÃÂÃ¢ÂÂÃÂÃ¢ÂÂ¢s biggest companies in certain sectors and industries are using countertrade techniques, as a method of internationalisation. The research uses a case study approach, to enable an in-depth understanding of the current attitudes towards and uses of countertrade. Six companies are studied in detail, representing the defence & aerospace, natural resources, engineering and industrial sectors.